2009
DOI: 10.1016/s1001-0742(08)62294-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of organic amendments on the sorption of pentachlorophenol on soils

Abstract: The influence of pH on the sorption of pentachlorophenol (PCP) onto three organic amendments, char, humic acid (HA) and peat, and the effect of organic amendments on PCP sorption to three kinds of soils were evaluated. The sorption of PCP on these sorbents fitted the Freundlich model well, suggesting that PCP sorption isotherms were nonlinear with exponential coefficient (N) value lower than 1. The PCP sorption capacity on three organic amendments and the N values increased with decreasing pH. The sorption cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…Furhermore, the lack of information within these studies to properly characterize the biochar material used further limits the ability to compare results. However, based on the analogous observations with non-biochar materials (Table 1), the overall conclusions are that biochar additions (Table 2) (Table 2); Li et al, 2009;Qiu et al, 2009b;Wang et al, 2009, ( Herbicides are much more than just weed killers. They may exhibit beneficial or adverse effects on other organisms.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Furhermore, the lack of information within these studies to properly characterize the biochar material used further limits the ability to compare results. However, based on the analogous observations with non-biochar materials (Table 1), the overall conclusions are that biochar additions (Table 2) (Table 2); Li et al, 2009;Qiu et al, 2009b;Wang et al, 2009, ( Herbicides are much more than just weed killers. They may exhibit beneficial or adverse effects on other organisms.…”
Section: Discussionmentioning
confidence: 91%
“…The highest sorption of pentachlorophenol in all the soils was observed when the soils were amended with char, followed by humic acids, and peat. Sorption was a function of organic carbon content (Li et al, 2009). The authors reported a 2.5-20 fold increase in the K f values following the char addition.…”
Section: Effect Of Carbonaceous Materials On Pesticide Sorptionmentioning
confidence: 97%
See 2 more Smart Citations
“…1a) which has no active functional groups to interact with the predominantly negatively charged PCP (pentachlorophenolate) species in solution (Fig. 5e right) which is its ionization state at the solution pH (6.5 ± 0.2) (Li et al, 2009). Thus, the two mechanisms thought to be responsible for the removal of PCP by SBA-15 are via very weak interactions with SBA-15 external wall surfaces, which accounts for very little PCP removal, and the filling of SBA-15 mesopores by charged PCP species in solution which was significant for SBA-15.…”
mentioning
confidence: 99%